COVID et Neuroleptiques : Lien Protecteur ? - ZIET , Chahrazed; SADOUKI , Yamina (Encadrant) (Université Sétif1 Ferhat Abbas. Faculté de Médecine. Département de Pharmacie, 2024)
Since December 2019, a 2019 coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has emerged in Wuhan and subsequently becomes a global epidemic. The virus can spread and be transmitted from one infected person to another directly or indirectly. Symptomatology varies from asymptomatic to more severe forms associated with complications such as acute respiratory distress syndrome, and in some cases can lead to death. Several diagnostic techniques have been developed and put on the market, including RTPCR which represents the reference method due to its sensitivity and specificity. Preventive measures are necessary, both individually (hand hygiene) and collectively (vaccination). However, no specific treatment to cure the infection is available to date. the hypothesis of a relationship between antipsychotic drugs and Covid-19 disease has been discussed in several studies, because numerous data have shown that they support and prove the role of these drugs in protection against infection by the latter and in the prevention of its severe and dangerous complications, and therefore antipsychotics can be a new treatment for Covid-19. These data have been confirmed by randomized trials, which are the result of the observation of the low incidence of Covid-19 and the low presence of severe complications in patients with psychological disorders at the level of. the psychiatry department. According to these first results which must still be reproduced on larger cohorts, which already suggest the possibility of a repositioning of neuroleptics..., justifying the possibility of considering them as a new treatment for Covid-19, and of studying the mechanism of their action in this role.
منذ ديسمبر ،2019ظهر مرض فيروس كورونا ( 2019كوفيد ( )19الناتج عن فيروس كورونا سارس - ،2 في مدينة ووهان ليصبح بعدها وباء عالميا. يمكن لهذا المرض أن ينتقل من شخص إلى آخر بطريقة مباشرة أو غير مباشرة تختلف الأعراض من حالة بدون اعراض خفيفة أو حالة متوسطة إلى حالة أكثر شدة مرفقة بمضاعفات مثل ضيق تنفسي حاد ، قد تؤدي في بعض الاحيان إلى الموت بغرض تشخيص المرض ، تم تطوير عدة طرق للفحص وطرحها في السوق ، حيث يعتبر فحص RT-PCRهو الطريقة المثلى نظرا لحساسيته و خصوصيته اتجاه الفيروس . التدابير الوقائية اساسية، وذلك على الصعيد الفردي) نظافة اليدين( كما على الصعيد الجماعي (التلقيح) لا يوجد لحد الآن دواء خاص بهذا المرض لهذا اللجوء إلى المركبات الموجودة يمكن أن يساعد في السيطرة على الوباء، تم مناقشة فرضية وجود علاقة بين الأدوية المضادة للذهان و المرض كوفيد - 19في عدة دراسات حيث أظهرت العديد من البيانات التي تؤيد و تثبت دور هذه الأدوية في الحماية من الإصابة بهذا الاخير او تطور الاصابة إلى المضاعفات الشديدة و الخطيرة لكوفيد -، 19و بالتالي يمكن أن تكون مضادات الذهان علاج جديد لكوفيد- 19اذا تم تأكيد هذه المعطيات عن طريق التجارب العشوائية التي كانت نتيجة ملاحظة قلة الإصابة ب كوفيد 19و و قلة وجود المضاعفات الخطيرة لدى المرضى ذوي الاضطرابات النفسية على مستوى قسم الطب النفسي . و من خلال هذه النتائج الأولية التي لا يزال يتعين تكرارها على مجموعات أكبرتم اقتراح إعادة تحديد موضع مضادات الذهان و تبرير إمكانية اعتبارها كعلاج جديد ل كوفيد- 19و دراسة تقنية عملها في هذا الدور
Keywords: COVID-19; SARS – COV 2; Neuroleptiques; lien; protection; prevention.